Celiac Disease and Eating Disorders are a Bidirectional Relationship of Diseases - Anatoly I. Khavkin; Nuriniso D. Odinaeva; Andrew V. Nalyotov; Elena I. Kondratyeva; Nataliya A. Marchenko; Alexander N. Matsynin; Ekaterina A. Yablokova; Kristina D. Zavrazhnaya (Педиатрическая фармакология, 2025)
Celiac disease and eating disorders are complex chronic diseases characterized by weight changes, malnutrition, and gastrointestinal symptoms. Celiac disease patients are treated by following a strict gluten-free diet, which may inadvertently contribute to eating disorders. Conversely, eating disorders can mask and aggravate the clinical manifestations of celiac disease, which leads to a prolongation of the diagnosis of the disease and problems with the treatment of such patients. The available data indicate an increased risk of developing eating disorders in patients with celiac disease and vice versa, suggesting a potential bidirectional relationship between these diseases. This review examines the mechanisms and clinical consequences of the interaction between celiac disease and eating disorders, and suggests strategies for comprehensive screening and treatment to improve the quality of life of patients with both conditions.